Family Achievements That Are Sakinah, Mawaddah, Warahmah - Sukmawati, Berlia; Khadafi, Mu’ammar (Faculty of Sharia, IAIN Metro, 2022)
There are many things about the sakinah, mawaddah, and warohmah families, but how do people recognize and apply these concepts, namely to the sakinah, mawaddah, and warohmah families that many married couples dream of the purpose of this research is to use qualitative research methods to find out the application of the sakinah mawaddah warahmah family concept and what factors influence the creation of a sakinah mawaddah warahmah family. This research uses a type of qualitative research, and the type of research is descriptive research. The results of the study show that the sakinah mawaddah warahmah family is formed on the basis of mutual understanding between men and women in marital relations, multiplying offspring, and developing human life on the ground of love and compassion. This will create peace, peace between the two. Basically, according to the Islamic view, the factor that aims to achieve a good family life is to create a peaceful and peaceful family environment.